2014
DOI: 10.1016/j.bbabio.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Glycerolipids in photosynthesis: Composition, synthesis and trafficking

Abstract: Glycerolipids constituting the matrix of photosynthetic membranes, from cyanobacteria to chloroplasts of eukaryotic cells, comprise monogalactosyldiacylglycerol, digalactosyldiacylglycerol, sulfoquinovosyldiacylglycerol and phosphatidylglycerol. This review covers our current knowledge on the structural and functional features of these lipids in various cellular models, from prokaryotes to eukaryotes. Their relative proportions in thylakoid membranes result from highly regulated and compartmentalized metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
268
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(287 citation statements)
references
References 134 publications
9
268
0
2
Order By: Relevance
“…MGDG 34:3, DGDG 34:3, and SQDG 34:3 were also very strongly represented in all three leaf stages. MGDG 34:6 species were detected, while DGDG 34:6 and SQDG 34:6 were either not present or below the detection limit, consistent with the current model for the desaturation of acyl chains of thylakoid lipids in the chloroplast (Li-Beisson et al, 2010;Boudière et al, 2014).…”
Section: Polar Lipid Profiles Change During Leaf Development and In Rsupporting
confidence: 61%
See 3 more Smart Citations
“…MGDG 34:3, DGDG 34:3, and SQDG 34:3 were also very strongly represented in all three leaf stages. MGDG 34:6 species were detected, while DGDG 34:6 and SQDG 34:6 were either not present or below the detection limit, consistent with the current model for the desaturation of acyl chains of thylakoid lipids in the chloroplast (Li-Beisson et al, 2010;Boudière et al, 2014).…”
Section: Polar Lipid Profiles Change During Leaf Development and In Rsupporting
confidence: 61%
“…This differs from the situation in Arabidopsis, where levels of all phospholipids show a positive correlation and all glycoglycerolipids show a negative correlation with Pi supply (Dörmann and Benning, 2002). By contrast, 36:x SQDG species, which are synthesized from the ER-derived secondary DAG pool in the chloroplast (Fritz et al, 2007;Li-Beisson et al, 2010;Boudière et al, 2014), clustered in group II (b) and showed the typically documented decrease with increasing Pi supply in H. prostrata. These contrasting responses resulted in an overall sulfolipid profile that responded very little to altered Pi availability.…”
Section: Chloroplast Lipid Metabolism Is Perturbed At Higher Leaf Pi mentioning
confidence: 48%
See 2 more Smart Citations
“…Thylakoid membrane lipids are central to photosynthetic function, including the stabilization of photosynthetic complexes and oxygen evolution (Jarvis et al, 2000;Jones, 2007;Leng et al, 2008;Mizusawa and Wada, 2012;Boudière et al, 2013). The most abundant classes are the neutral lipids monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG) and the anionic lipids sulfoquinovosyldiacylglycerol (SQGD) and phosphatidylglycerol (PG; Frentzen, 2004;Shimojima et al, 2010;Mizusawa and Wada, 2012).…”
mentioning
confidence: 99%